2005
DOI: 10.1007/s10509-005-4320-7
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Study Of W Uma Type Binary In The Old Cluster Ngc 6791

Abstract: Study of eclipsing binaries in an open cluster offer information regarding the age of the cluster in addition to the component stars. In this paper we present the analysis of a W UMa system discovered in the open cluster NGC 6791 using the Wilson-Devinney (W-D) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The photometric mass ratios of variables in Be 33, NGC 6791, Be39 and NGC 7789 suggest that most of them are W-subtype with mass ratio q > 1 or intermediate mass ratio values, independent of the respective cluster age (Rukmini & Vivekananda Rao 2002;Rukmini et al 2005;Sriram et al 2009;Sriram & Vivekananda Rao 2010). This work, along with our previous ones, suggests that the frequency of W-type systems is high compared to the frequency of A-type ones in clusters, which supports the theoretical evolutionary idea that A-type systems evolve into W-types.…”
Section: Discussionmentioning
confidence: 99%
“…The photometric mass ratios of variables in Be 33, NGC 6791, Be39 and NGC 7789 suggest that most of them are W-subtype with mass ratio q > 1 or intermediate mass ratio values, independent of the respective cluster age (Rukmini & Vivekananda Rao 2002;Rukmini et al 2005;Sriram et al 2009;Sriram & Vivekananda Rao 2010). This work, along with our previous ones, suggests that the frequency of W-type systems is high compared to the frequency of A-type ones in clusters, which supports the theoretical evolutionary idea that A-type systems evolve into W-types.…”
Section: Discussionmentioning
confidence: 99%
“…Since no systematic photometric analysis has been carried out to derive the system parameters, especially the mass-ratio for these W UMa type variables discovered in LMC, we have analyzed the light curves of six eclipsing binary systems: S1 (OGLE 053247.54-694403.1), S2 (OGLE 053251.73-700256.2), S3 (OGLE 051206.93-685645.1), S4 (OGLE 050542.01-691725.9), S5 (OGLE 053540.37-695413.9) and S6 . A similar kind of study was carried out on the W UMa type binaries in open clusters: NGC 7789 (Sriram & Vivekananda Rao 2010), Be 39 (Sriram et al 2009), NGC 6791 (Rukmini et al 2005), and Be 33 (Rukmini & Vivekananda Rao 2002). We have used the Wilson-Devinney (W-D) program to derive the various photometric elements and put a constraint on the mass-ratio parameter.…”
Section: Introductionmentioning
confidence: 96%
“…From the analysis performed on these systems, it was found that the mass-ratios were close to unity and in one case greater than unity (Rukmini & Vivekananda Rao 2002, Rukmini et al 2005. A detail spectroscopic observation was suggested to know the true nature of these objects.…”
Section: Introductionmentioning
confidence: 97%
“…The old open cluster Berkeley 39 is located in the direction of the galactic anti-centre (α 2000 =7 h 46 m 48 s , and Be 33 (Rukmini & Vivekananda Rao 2002, Rukmini et al 2005. From the analysis performed on these systems, it was found that the mass-ratios were close to unity and in one case greater than unity (Rukmini & Vivekananda Rao 2002, Rukmini et al 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation